A novel preparation of natural rubber films with a conducting nanocarbon network for antistatic applications. (March 2023) - Wiroonpochit, Panithi; Keawmaungkom, Sutthinee; Chisti, Yusuf; Hansupalak, Nanthiya
Abstract: Natural rubber (NR) films with antistatic properties were made using a new, environmentally less burdensome process compared to the traditional methods. For making the films, the NR latex was prevulcanized by ultraviolet light using a sulfur-free method and composited with acid-purified multiwall carbon nanotubes (p-MWCNT) to develop antistatic properties. The process variables included: the type of surfactant (sodium dodecyl sulfate (SDS) and 3 others) used in dispersing p-MWCNT in NR latex, the p-MWCNT-to-surfactant mass ratio, and the loading of p-MWCNT in the NR latex. These variables were optimized to obtain films with acceptable mechanical and electrical properties. The replacement of the traditionally used hydrochloric acid with a relatively benign acetic acid was investigated for purification of MWCNT to p-MWCNT. The results revealed that the optimal conditions for producing films with acceptable properties were: SDS as the preferred surfactant because of its molecular structure; a MWCNT:SDS mass ratio of 1:0.5; and 0.33 g of p-MWCNT per 100 g NR. The amount of SDS used was crucial for producing films with the desired properties: an excess of SDS adversely impacted the integrity of the composite films, whereas too little SDS failed to uniformly disperse the filler (p-MWCNT) in the films. The NR needed to be prevulcanized in a separate prior step without the MWCNT, to ensure development of superior electrically conducting pathways in the film. Concentrated hydrochloric acid typically used in purifying MWCNT was effectively replaced with glacial acetic acid. Graphical Abstract: ga1 Highlights: Antistatic composite films were made of natural rubber and carbon nanotubes. Formulations were optimized for making acceptable films with minimum materials. Conventional method of purifying carbon nanotubes was replaced with a greener one. Hydrochloric acid could be discarded in favor of the greener acetic acid.